The German bestseller in the late nineteenth century - Woodford, Charlotte; Schofield, Benedict (Studies in German literature, linguistics, and culture., 2012)
"The late nineteenth century was a crucial period for the development of German fiction. Political unification and industrialization were accompanied by the rise of a mass market for German literature, and with it the beginnings of the German bestseller. Offering escape, romance, or adventure, as well as insights into the modern world, nineteenth-century bestsellers often captured the imagination of readers well into the twentieth century and beyond. However, many have been neglected by scholars. This volume offers new readings of literary realism by focusing not on the accepted intellectual canon but on commercially successful fiction in its material and social contexts. It investigates bestsellers from writers such as Freytag, Dahn, Jensen, Raabe, Viebig, Stifter, Auerbach, Storm, Möllhausen, Marlitt, Suttner, and Thomas Mann. The contributions examine the aesthetic strategies that made the works such a success, and writers' attempts to appeal simultaneously on different levels to different readers. Bestselling writers often sought to accommodate the expectations of publishers and the marketplace, while preserving some sense of artistic integrity. This volume sheds light on the important effect of the mass market on the writing not just of popular works, but of German prose fiction on all levels. Contributors: Christiane Arndt, Caroline Bland, Elizabeth Boa, Anita Bunyan, Katrin Kohl, Todd Kontje, Peter C. Pfeiffer, Nicholas Saul, Benedict Schofield, Ernest Schonfield, Martin Swales, Charlotte Woodford. Charlotte Woodford is Fellow and Lecturer in German at Selwyn College, University of Cambridge. Benedict Schofield is Lecturer in German and Senior Tutor for the School of Arts and Humanities at King's College London."--Publisher's description.